2015
DOI: 10.1038/ncomms7332
|View full text |Cite
|
Sign up to set email alerts
|

Alendronate inhalation ameliorates elastase-induced pulmonary emphysema in mice by induction of apoptosis of alveolar macrophages

Abstract: Alveolar macrophages play a crucial role in the pathogenesis of emphysema, for which there is currently no effective treatment. Bisphosphonates are widely used to treat osteoclastmediated bone diseases. Here we show that delivery of the nitrogen-containing bisphosphonate alendronate via aerosol inhalation ameliorates elastase-induced emphysema in mice. Inhaled, but not orally ingested, alendronate inhibits airspace enlargement after elastase instillation, and induces apoptosis of macrophages in bronchoalveolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 35 publications
5
57
1
Order By: Relevance
“…As alveolar fibroblasts are the major p19 ARF ‐expressing cells in the lung (Figure 1f; Hashimoto et al, 2016), these cells likely affected the expression of MMP‐12 and TIMP‐2 cell nonautonomously through SASP. Consistent with previous findings (Limjunyawong et al, 2015; Ueno et al, 2015), the expression of these genes was mostly diminished after 3 weeks, and DT also had a minor effect on these genes at this time point (Figures 5b and S5b). Collectively, these results suggest that the presence of p19 ARF ‐expressing cells in lung tissues facilitates the accumulation of inflammatory cells during the early phase of a PPE challenge, which promotes the development of emphysema‐associated pathologies.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…As alveolar fibroblasts are the major p19 ARF ‐expressing cells in the lung (Figure 1f; Hashimoto et al, 2016), these cells likely affected the expression of MMP‐12 and TIMP‐2 cell nonautonomously through SASP. Consistent with previous findings (Limjunyawong et al, 2015; Ueno et al, 2015), the expression of these genes was mostly diminished after 3 weeks, and DT also had a minor effect on these genes at this time point (Figures 5b and S5b). Collectively, these results suggest that the presence of p19 ARF ‐expressing cells in lung tissues facilitates the accumulation of inflammatory cells during the early phase of a PPE challenge, which promotes the development of emphysema‐associated pathologies.…”
Section: Resultssupporting
confidence: 92%
“…Although a significant change was observed in lung morphology and function 3 weeks after the administration of PPE (Figures 2 and 3), no significant difference was found in the number or composition of inflammatory cells in BALF among PPE‐ and/or DT‐treated samples at this time point (Figure S3). This result was expected because a single shot of PPE only has temporal effects on BALF cells in the C57BL/6J strain (Limjunyawong, Craig, Lagassé, Scott, & Mitzner, 2015; Ueno et al, 2015). Therefore, we analyzed BALF cells at an earlier time point after the administration of PPE.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Our results point out that bisphosphonate strongly impacts senescent phenotype reinforcing a potential functional link between bone fragility during aging and increase cellular senescence. It has also been reported that bisphosphonates can impact bone‐independent marks of aging like emphysema (Ueno et al, 2015), emphysema being thought to be regulated by cellular senescence (Taraseviciene‐Stewart, & Voelkel, 2008), further suggesting that FDPS/bisphosphonates can regulate cellular senescence and aging beyond their well‐known bone effects.…”
Section: Discussionmentioning
confidence: 97%